2009
DOI: 10.1111/j.1468-0394.2009.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of electroencephalographic entrainment using thalamocortical modelling

Abstract: The concept of linked oscillators in biological control systems has long been established. Frequency entrainment is a predominant explanation behind many biological rhythms. In this paper a preliminary examination of electroencephalographic entrainment is made to survey the possibility and methods of achieving signal entrainment at the highest level of neurological organization and function. A model of the thalamocortical system is employed to generate simulated electroencephalographic signals and is tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Research findings suggest that music and sound can modulate autonomic arousal through entrainment ( Trost and Vuilleumier, 2013 ; Regaçone et al, 2014 ). Entrainment is a process through which two autonomous rhythmic oscillators with similar but different fundamental frequencies interact, resonate, and synchronize ( Cvetkovic et al, 2009 ). Classic examples of entrainment include the synchronizing of human sleep-wake cycles to the 24-h cycle of light and dark ( Clayton et al, 2005 ), the synchronization of a heartbeat to a cardiac pacemaker ( Cvetkovic et al, 2009 ), and the use of rhythmic auditory stimulation in the rehabilitation of motor functions ( Thaut and Abiru, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research findings suggest that music and sound can modulate autonomic arousal through entrainment ( Trost and Vuilleumier, 2013 ; Regaçone et al, 2014 ). Entrainment is a process through which two autonomous rhythmic oscillators with similar but different fundamental frequencies interact, resonate, and synchronize ( Cvetkovic et al, 2009 ). Classic examples of entrainment include the synchronizing of human sleep-wake cycles to the 24-h cycle of light and dark ( Clayton et al, 2005 ), the synchronization of a heartbeat to a cardiac pacemaker ( Cvetkovic et al, 2009 ), and the use of rhythmic auditory stimulation in the rehabilitation of motor functions ( Thaut and Abiru, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…shown that I-dosing precipitates auditory driving with self-reported subjective experience of emotional and cognitive state [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%